The Effect of Financial Literacy, Entrepreneurial Characteristics, and Financial Inclusion on Business Performance - Dina Kusumawati; Dwi Erlin Effendi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Objective: Delays in business management make it difficult for the continued development of MSMEs. This study aims are analyzes financial literacy, entrepreneurial characteristics, and financial inclusion in business performance in processing industry SMEs in Jepara Regency. Research Design & Methods: The data used were obtained from interviews using a questionnaire. The number of samples used was 100 MSME actors selected by the Non-Probability Sampling technique. Data analysis was performed using multiple linear regression analysis methods. Findings: The results showed that financial literacy had a positive and significant effect on business performance, entrepreneurial characteristics had a positive and significant effect on business performance, financial inclusion had a positive and significant effect on business performance, and simultaneously, financial literacy, entrepreneurial characteristics, and financial inclusion had an effect on business performance. Implications and Recommendations: This research implies that the level of financial literacy will affect the making of important decisions in managing business finances, so MSME actors need to increase their financial literacy. The characteristics of a good entrepreneur owned by someone will have a positive orientation toward business performance. Good financial inclusion means that it is easy to use financial services so that they can help overcome problems in their business.